(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
The scope of University Extension, linked to teaching and research inseparably, comprises an important strategy for the personal and professional training of academics. The elaboration of this work through an experience report, seeks to present the author’s personal and professional trajectory and its relationship with the University Extension mainly with the Rondon Project. This project has a fundamental role in their academic formation, since in a transformative way it allowed the understanding of the different possibilities of insertion of the nursing professional in the communities, as well as the overcoming of several professional obstacles throughout his career and his life.